Encapsulation of Heteropolyanion‐Based Ionic Liquid within the Metal–Organic Framework MIL‐100(Fe) for Biodiesel Production. Issue 3 (16th December 2014) - Wan, Hui; Chen, Chong; Wu, Zuowang; Que, Yigen; Feng, Yu; Wang, Wei; Wang, Lei; Guan, Guofeng; Liu, Xiaoqin
Abstract A new strategy was proposed to construct the ionic liquid, polyoxometalate (POM), and metal–organic framework (MOF) composite. The POM‐based MOF was synthesized by using the direct hydrothermal method. The sulfonic acid group‐functionalized ionic liquid was used for further modification of the hybrid material to realize the encapsulation of the heteropolyanion‐based ionic liquid within the cages of the MOF. The catalysts were characterized by using XRD, N2 adsorption–desorption, FTIR, SEM, TEM, elemental analysis, and TGA. The results indicated that the heteropolyanion‐based ionic liquid had been successfully encapsulated within the cages and the structure of MIL‐100 (MIL=Materials of Institut Lavoisier) remained intact. The POM–ionic‐liquid‐functionalized MOF, with high content of the active component, had both Lewis and Brønsted acid sites, which led to high catalytic activity for the esterification of oleic acid with ethanol. The esterification reaction conditions were optimized by using response surface methodology (RSM), and the corresponding conversion of oleic acid reached 94.6 %. The catalyst could be easily recovered and reused six times without significant loss of activity.